Research on ontology based data integration of land use - CHEN Jian-jie; YE Zhi-xuan; KE Zheng-yi (浙江大学学报. 农业与生命科学版)
In order to study social and economic development impact on the use of land resources dynamically, it must realize knowledge sharing and data integration for land use information, especially must find a way of resolving the semantic interoperation of distributed heterogeneous systems. This paper explored a land use reference model and expressed the semantic of domain knowledge distinctly based on the ontology technology, and used OWL (Ontology Web Language) to describe the partial of land use feature ontology. The research had achieved the purpose for knowledge sharing and semantic interoperation effectively, in addition, the paper gave an elementary process and main algorithms for land use data integration based on the ontology, and used a Multi-Agent method to develop a prototype.